2011
DOI: 10.1139/g11-015
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of landraces in foxtail millet (Setaria italica(L.) P. Beauv.) revealed with transposon display and interpretation to crop evolution of foxtail millet

Abstract: Origin and domestication process of foxtail millet [Setaria italica (L.) P. Beauv.] have been studied by several groups but still in discussion with ambiguity. It is cardinal to elucidate the issue by studying large number of accessions with enough number of markers covering the whole genomic regions. Genetic structures were analyzed by transposon display (TD) using 425 landraces of foxtail millet and 12 accessions of the wild ancestor, green foxtail. We applied three recently-active transposons as genome-wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 37 publications
1
31
0
1
Order By: Relevance
“…Similarly, Hirano et al (2011) employed transposons to determine the correlation between geographical area and genetic structure. However, these genetic markers represent limited information regarding genomic polymorphism (Wright and Gaut, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Hirano et al (2011) employed transposons to determine the correlation between geographical area and genetic structure. However, these genetic markers represent limited information regarding genomic polymorphism (Wright and Gaut, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…(1995) investigated the genetic diversity and structure of green foxtail accessions collected from North America and Eurasia using allozyme markers, and suggested that there were similar isozymatic forms between foxtail millet and green foxtail collected from the same regions. Chinese accessions were identified as having a high level of genetic diversity using amplified fragment length polymorphism (AFLP) markers (Le Thierry d’Ennequin et al ., 2000), transposon display (Hirano et al ., 2011), and intersimple sequence repeat (ISSR) markers (Li et al ., 2012), and the well known A10 accession which was used as a model for C 4 photosynthesis study was also from China (Brutnell et al ., 2010; Li and Brutnell, 2011; Bennetzen et al ., 2012; Caemmerer et al ., 2012). However, all these studies were carried out with a small sample size of no more than 40 accessions.…”
Section: Introductionmentioning
confidence: 99%
“…It is able to endure droughts and grows quickly; therefore, the indigenous people cultivate foxtail millet instead of rice. Though several researches have used a few millet strains from Taiwan, little is known about the genetic diversity in hundreds of local landraces scattered throughout Taiwan [1,2]. …”
Section: Introductionmentioning
confidence: 99%